The Impacts of Othering on the Hybrids and Their Coping Mechanisms in Tokyo Ghoul - Michael; Liem Satya Limanta (Kata Kita: Journal of Language, Literature, and Teaching, 2026)
This paper analyzes the impacts of othering on human-ghoul hybrids in Tokyo Ghoul and the coping mechanisms they develop to deal with the impacts. The topic was chosen because the text’s plot is directly driven by the impacts of othering. The applied concepts are taken from Said’s “othering”, Bhabha’s mimicry, hybridity & ambivalence, and Glissant’s rhizomatic identity. The main impacts of othering are alienation and aggression. Alienation forces hybrids into a normless state, in which they are powerless. They become more aggressive to resist threats posed by humans and ghouls. The main coping mechanism developed by the hybrids is to build identities that mimic the pure parties. In conclusion, the hybrids experience othering. Therefore, they are alienated and are forced to become aggressive to resist the othering. The aforementioned factors impact the hybrids negatively. Thus, they cope by mimicking the norms of the “self” to develop rhizomatic identities.